Uapaca kirkiana, an indigenous fruit tree in sub-Saharan Africa: A comprehensive review - Armistice Chawafambira; Mahmood Moosa Sedibe; Augustine Mpofu; Matthew Achilonu (Cogent Food & Agriculture, 2020)
Uapaca kirkiana is an indigenous fruit tree that grows in hot and dry areas in sub-Saharan Africa. The tree tolerates dry conditions, high temperatures and acts as a food source for people that live in drier conditions were exotic fruit trees can hardly survive. The tree produced fruits that are rich in essential minerals and has a potential to act as a source of vitamin C. Ripe fruits are eaten raw and mostly sold at local and roadside markets with no processing. Traditionally the fruit can be processed into various products which include alcoholic and non-alcoholic beverages and traditional cakes. The fruit has a potential to improve nutritional status, food security, and livelihoods of rural dwellers especially in arid and semi-arid areas. However, the contribution of the fruit to human nutrition is often not recognised. The fruit, like most indigenous fruits, has limited and out-dated data on nutrient composition. Indigenous knowledge on handling and uses of the fruit needs to be upgraded. This review attempts to contribute to this effort by evaluating the existing evidence on its nutritional potential, functional and bioactive properties, processing, postharvest handling with the aim of identifying possible areas of research and its utilisation.